Peningkatan Pembelajaran Melalui Situs Media Online dengan Metode Blended Learning Pada Masyarakat Desa Bojongcae - Indri Arrafi Juliannisa (Journal of Dedicators Community, 2020)
This community service activity is intended to provide more knowledge to the residents of Bojongcae- Lebak Regency, especially for parents, and children and teenagers who relied on manual and limited teaching material for education with increasing the ability of partner groups in the world of education. The partner groups in this study are housewives who are members of the PKK group, and teenagers who have the ability to speak English better than housewives and other teenagers.The material provided in this community service program is internet based using social media instragram with the account name "ayokita.belajar". The material chosen by the service team are learning of English language and learning of skills related to daily needs, the selection of material and social media was agreed by the partner group, with this activity the partner group is expected to be able to provide teaching materials more creative, innovative and easily understood. Moreover, addition of knowledge about study by e-learning is expected that the process of providing subject matter can be more modern and follow more sophisticated technological developments. The result of this community service activity is that partner groups can create a training or learning activity with English-language material and training videos to improve their daily skills. Measurement of learning with social media have done by way of children and adolescents given questions about material that has been uploaded on social media Instagram